A PEG / PLA high-thermal-conductivity degradable composite film, a preparation method and application thereof
Patent Information
- Application Number
- CN202611156188.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]现有技术直接将未改性Al2O3、BN与PEG/PLA物理共混,存在多重缺陷:其一,无机填料与有机基体界面相容性差,填料易发生团聚,在基体内部形成缺陷与孔洞;其二,填料与基体、填料之间界面热阻大,声子散射严重,无法充分发挥填料的导热优势;其三,刚性无机Al2O3颗粒、BN纳米片层穿插于PLA、PEG高分子链之间,会形成大量物理束缚位点,限制分子链可逆拉伸与松弛运动;填充量越高、填料团聚越严重,分子链运动阻力越大,直接造成薄膜形状固定率、形状回复率显著下降,出现“导热提升则形状记忆性能劣化”的相互制约矛盾;现有研究仅单一追求导热性能提升,完全忽视该冲突,创新思路高度同质化,无法兼顾两种核心功能;其四,填料团聚与界面缺陷会破坏基体连续性,同步劣化材料力学性能
(1)界面协同改性,降低界面热阻;
Smart Images

Figure CN122978672A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable polymer functional composite materials technology, specifically relating to a PEG / PLA high thermal conductivity biodegradable composite film, its preparation method, and its application. Background Technology
[0002] As electronic devices develop towards miniaturization, high integration, and high power density, heat dissipation has become a key factor restricting their lifespan and safety. At the same time, the environmental pollution caused by disposable polymer materials is becoming increasingly serious, making polymer-based composite materials with thermal conductivity, thermally induced shape memory, and biodegradability a research hotspot.
[0003] Polylactic acid (PLA) is a bio-based biodegradable polymer material with excellent biocompatibility and processing performance, but it is inherently brittle and has poor thermal conductivity. Polyethylene glycol (PEG) is a commonly used plasticizer for PLA, which can significantly improve PLA's toughness. Furthermore, the PEG / PLA blend system naturally possesses excellent thermally induced shape memory effect, allowing for stable reversible deformation under external force deformation, low-temperature setting, and temperature recovery conditions, making it an ideal substrate for smart films. However, the low thermal conductivity of pure PEG / PLA matrix cannot meet the requirements of electronic thermal management applications.
[0004] To improve the thermal conductivity of polymers, two types of inorganic non-metallic thermally conductive fillers are typically introduced into the matrix: alumina (Al2O3) and hexagonal boron nitride (BN). Alumina exhibits excellent chemical stability, thermal stability, and electrical insulation properties, and is inexpensive; hexagonal boron nitride possesses ultra-high intrinsic thermal conductivity, and its two-dimensional layered structure facilitates the creation of continuous thermal conductive pathways within the matrix. Both are commonly used fillers in polymer-based thermally conductive composite materials.
[0005] Existing technologies that directly physical blend unmodified Al2O3, BN, and PEG / PLA have several drawbacks: First, the inorganic filler has poor interfacial compatibility with the organic matrix, making it prone to agglomeration and forming defects and pores within the matrix. Second, the high interfacial thermal resistance between the filler and the matrix, and between the filler itself, leads to severe phonon scattering, preventing the full utilization of the filler's thermal conductivity advantage. Third, the rigid inorganic Al2O3 particles and BN nanosheets interspersed between PLA and PEG polymer chains form numerous physical binding sites, restricting the reversible stretching and relaxation of the molecular chains. Higher filler content and more severe filler agglomeration result in greater resistance to molecular chain movement, directly causing a significant decrease in film shape fixation and shape recovery rates, creating a contradictory situation where "improved thermal conductivity leads to deterioration of shape memory performance." Current research focuses solely on improving thermal conductivity, completely ignoring this conflict, resulting in highly homogenized innovative approaches that fail to address both core functions simultaneously. Fourth, filler agglomeration and interfacial defects disrupt matrix continuity, simultaneously degrading the material's mechanical properties.
[0006] The improvement in thermal conductivity of a purely physical blend system is limited and inevitably sacrifices shape memory function. Therefore, there is an urgent need to develop a preparation scheme with interface optimization and filler synergy, which can significantly improve thermal conductivity while avoiding the damage to shape memory performance by inorganic fillers, and at the same time retain the excellent mechanical and biodegradable properties of the material. Summary of the Invention
[0007] Based on the aforementioned shortcomings and deficiencies in the existing technology, one of the objectives of this invention is to at least solve one or more of the aforementioned problems in the existing technology. In other words, one of the objectives of this invention is to provide a PEG / PLA high thermal conductivity biodegradable composite film that meets one or more of the aforementioned requirements, as well as its preparation method and application. The multifunctional composite film uses polylactic acid PLA / polyethylene glycol PEG blend as the matrix and interface-modified alumina Al2O3 / hexagonal boron nitride BN as the thermally conductive filler. It simultaneously possesses multiple functions such as thermal conductivity, thermally induced shape memory, and biodegradability, and is suitable for thermal management deformation scenarios such as flexible electronics and biodegradable smart packaging.
[0008] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A PEG / PLA high thermal conductivity biodegradable composite film includes an organic matrix phase and a modified inorganic non-metallic thermally conductive filler distributed in the organic matrix phase. The organic matrix phase is a blend of polylactic acid (PLA) and polyethylene glycol (PEG). The modified inorganic non-metallic thermally conductive filler is a composite filler consisting of γ-glycidoxypropyltrimethoxysilane-modified alumina K-Al2O3 and γ-aminopropyltriethoxysilane-modified hexagonal boron nitride K-BN.
[0009] As a preferred option, based on a total mass of 100 parts, the mass ratio of each component is as follows: PLA 59.5-68 parts, PEG 10.5-12 parts, K-Al2O3 5-10 parts, and K-BN 10-20 parts.
[0010] The present invention also provides a method for preparing the PEG / PLA high thermal conductivity biodegradable composite film as described above, comprising the following steps: (1) K-Al2O3 and K-BN were prepared by surface grafting modification of Al2O3 and BN respectively using γ-glycidoxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane. (2) K-Al2O3 and K-BN were added to anhydrous ethanol, stirred and ultrasonically dispersed, and then dried to remove the solvent to obtain modified inorganic non-metallic thermally conductive filler. (3) The dried PLA and PEG are mixed evenly with the modified inorganic non-metallic thermally conductive filler, and then melt-blended, extruded and pelletized to obtain composite granules; (4) The composite granules are hot-pressed to obtain a PEG / PLA high thermal conductivity biodegradable composite film.
[0011] As a preferred embodiment, the surface grafting modification process in step (1) includes: The silane coupling agent γ-glycidoxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane was added to a mixture of anhydrous ethanol and water, and the pH was adjusted to 4.5-5.5 with glacial acetic acid. The mixture was pre-hydrolyzed at room temperature for 10-30 min. The corresponding filler, alumina Al2O3 or hexagonal boron nitride BN, was added, and the mixture was stirred at 60-80℃ for 2-4 h. After filtration, the mixture was washed with anhydrous ethanol and dried under vacuum to obtain K-Al2O3 or K-BN.
[0012] As a preferred embodiment, the amount of the silane coupling agent added is 3 to 5 wt% of the filler mass.
[0013] As a preferred embodiment, the volume ratio of anhydrous ethanol to water in the mixture is (90-95):(5-10) per 100 parts by volume.
[0014] As a preferred embodiment, the particle size of Al2O3 is 5-10 μm, and the particle size of BN is 25 μm.
[0015] As a preferred embodiment, step (3) is carried out in a twin-screw extruder, and the temperatures of the three heating zones are set to 155°C, 160°C and 165°C respectively.
[0016] As a preferred embodiment, in step (4), the hot pressing temperature is 160-180℃, the pressure is 5-10MPa, the preheating time is 5-10min, and the hot pressing time is 5-10min.
[0017] The present invention also provides applications of PEG / PLA high thermal conductivity biodegradable composite films as described in any of the preceding embodiments or PEG / PLA high thermal conductivity biodegradable composite films prepared by the preparation method described in any of the preceding embodiments, for use in flexible electronics, wearable devices, electronic packaging, thermal management materials, and biodegradable shape memory smart packaging materials.
[0018] Compared with the prior art, the beneficial effects of this invention are: (1) Interface co-modification to reduce interface thermal resistance; This invention uses KH560 to modify Al2O3 and KH550 to modify BN, and introduces epoxy and amino groups onto the filler surface, respectively. During melt blending and hot pressing, an amino-epoxy ring-opening reaction occurs to construct a K-Al2O3-K-BN interfacial bridging structure. This not only improves the compatibility between the filler and the PEG / PLA matrix and inhibits filler agglomeration, but also reduces the interfacial thermal resistance between fillers and between the filler and the matrix, thus significantly improving heat transfer efficiency. (2) Dual packing materials work together to construct a continuous heat conduction network; The sheet-like BN of this invention serves as the main thermally conductive framework, constructing an in-plane thermally conductive pathway; granular Al2O3 fills the gaps between the BN sheets, acting as a bridge, and the two form a particle-sheet synergistic thermally conductive network; the optimal formulation sample has a room temperature thermal conductivity of 0.815 W / (m·K), which is 3.67 times that of the pure PEG / PLA matrix; (3) Simultaneously considers thermal conductivity and excellent shape memory performance; Existing technical research shows that simply filling with inorganic fillers will severely reduce the film shape fixation rate and recovery rate. The flexible interface bridging layer of this invention weakens the binding of rigid fillers on polymer chains. With precise filler ratio, the film shape fixation rate and recovery rate only decrease slightly under a 20wt% inorganic filler load. Under a high inorganic filler load of 30wt%, it can still retain good thermally induced reversible deformation function, breaking through the technical bottleneck that thermal conductivity and shape memory are incompatible. (4) The process is simple and easy to industrialize and promote; This invention employs a traditional melt blending + hot pressing process, which has low equipment requirements, a short process flow, and easily controllable process parameters. The raw materials are all commercially available and common, resulting in low production costs and suitability for large-scale production. (5) Wide range of applicable scenarios; The PEG / PLA high thermal conductivity biodegradable composite film of the present invention possesses four major properties: insulation, thermal conductivity, thermally induced shape memory, and biodegradability. It breaks through the limitation of the single function of traditional PLA-based films and is suitable for use in multiple fields such as flexible electronics, wearable devices, electronic heat dissipation, and biodegradable smart packaging. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the preparation process of the PEG / PLA high thermal conductivity biodegradable composite film of the present invention; Figure 2 This is a reaction mechanism diagram of the surface modification of Al2O3 and BN with silane coupling agent according to the present invention; Figure 3 This diagram illustrates the interfacial bridging reaction and thermal network formation mechanism of K-Al2O3 and K-BN during the melt blending process of this invention. Detailed Implementation
[0020] The following provides a detailed description of the PEG / PLA high thermal conductivity biodegradable composite film of the present invention, its preparation method, and its applications.
[0021] This invention addresses the problems of existing PEG / PLA-based shape memory composite films directly filled with unmodified Al2O3 and BN thermally conductive fillers, which suffer from filler agglomeration, high interfacial thermal resistance leading to limited thermal conductivity improvement, rigid inorganic fillers constraining polymer chains and significantly degrading the film's shape memory performance, making it difficult to reconcile thermal conductivity and shape memory functions. Furthermore, filler agglomeration can easily cause stress concentration and degrade the material's mechanical properties. This invention provides an interfacially synergistically modified Al2O3 / BN-filled PEG / PLA multifunctional composite film.
[0022] The core innovative design of this invention involves using two different silane coupling agents to differentially modify the surfaces of Al2O3 and BN. The epoxy and amino active groups on the filler surface undergo ring-opening reactions during melt processing, constructing a flexible organic interface bridging layer between fillers. This weakens the physical constraint of rigid fillers on PLA / PEG segments. Combined with a defined filler compound ratio, the film retains excellent thermally induced shape memory properties while achieving high inorganic filler loading and significantly improved thermal conductivity. Simultaneously, the particle-layer filler synergistically constructs a three-dimensional thermally conductive network, simultaneously improving the material's mechanical strength and toughness, thus resolving the problem of conflicting properties in existing technologies.
[0023] Specifically, the interface-synergistic modified Al2O3 / BN filled PEG / PLA high thermal conductivity biodegradable composite film of the present invention consists of a matrix and modified inorganic non-metallic thermally conductive fillers. The matrix is a blend of polylactic acid PLA and polyethylene glycol PEG, and the modified inorganic non-metallic thermally conductive filler is a composite filler of γ-glycidyl etheroxypropyltrimethoxysilane KH560 modified alumina K-Al2O3 and γ-aminopropyltriethoxysilane KH550 modified hexagonal boron nitride K-BN.
[0024] The preferred proportions of each raw material component by mass percentage are: PLA 59.5–68%, PEG 10.5–12%, K-Al2O3 5–10%, and K-BN 10–20%; wherein the mass ratio of PLA to PEG is fixed at 85:15. The raw material parameters are as follows: PLA weight-average molecular weight Mw = 250,000 g / mol, PEG number-average molecular weight Mn = 6,000 g / mol; Al2O3 particle size 5-10 μm, purity ≥ 99.9 wt%; BN particle size 25 μm, purity ≥ 99.9 wt%; KH560 and KH550 addition amounts are 3-5 wt% of the corresponding filler mass, which can be determined according to actual application requirements.
[0025] The method for preparing the interface-synergistically modified Al2O3 / BN filled PEG / PLA high thermal conductivity biodegradable composite film of the present invention includes the following steps: (1) Raw material pretreatment; PLA particles and PEG powder were placed in a vacuum oven and dried at 60°C for 8 hours to remove surface adsorbed moisture; raw Al2O3 and BN powders were placed in a vacuum oven and dried at 120°C for 12 hours. After drying, they were sealed and stored to prevent secondary water absorption. (2) Surface modification of inorganic fillers; Take KH560 and KH550 respectively, add anhydrous ethanol / deionized water mixture, adjust the pH of the system to 4.5-5.5 with glacial acetic acid, stir at room temperature for 10-30 min to complete the pre-hydrolysis of silane coupling agent; Wherein, based on 100 parts by volume, the volume ratio of anhydrous ethanol to water in the mixture is (90-95):(5-10), preferably a volume ratio of 95:5; The dried fillers Al2O3 and BN were added to the corresponding coupling agent hydrolysate, and after being ultrasonically dispersed evenly, the mixture was stirred at 60-80℃ for 2-4 hours. The amount of silane coupling agent added is 3 to 5 wt% of the filler mass, which can be determined according to the actual application requirements. The reaction system was filtered, and the filter cake was washed three times with anhydrous ethanol to remove unreacted coupling agent. The mixture was then dried under vacuum at 80°C for 12 hours to obtain K-Al2O3 (KH560 modified alumina) and K-BN (KH550 modified hexagonal boron nitride), respectively.
[0026] After hydrolysis, KH560 forms Si-O-Al bonds with the hydroxyl groups on the Al2O3 surface, while retaining epoxy groups on the surface; after hydrolysis, KH550 binds to the active sites on the BN surface, introducing amino groups to the surface, providing active sites for subsequent interfacial reactions between fillers. (3) Premixing of compound fillers; The prepared K-Al2O3 and K-BN were added to anhydrous ethanol in a certain ratio, and the mixture was dispersed by stirring and ultrasonication to ensure that the two fillers were mixed evenly. Then the solvent was removed by drying to obtain the composite modified filler. (4) Melt blending and granulation; The dried PLA, PEG and compound modified filler were mechanically mixed evenly and fed into a micro twin-screw extruder. The three temperature zones were set to 155℃, 160℃ and 165℃ respectively. The mixture was melt-blended and extruded into pellets. The extrusion was repeated twice to improve the uniformity of the material mixing and obtain composite pellets. (5) Hot pressing; Weigh a certain amount of composite granules and place them into a mold, then place the mold in a flat vulcanizing machine. Process parameters: temperature 160-180℃, pressure 5-10MPa, preheat for 5-10 minutes, then hot press for 5-10 minutes. After naturally cooling to room temperature, demold the film and obtain composite films of different thicknesses according to the mold size. The 0.55mm film is used for thermal conductivity testing, and the 0.15mm film is used for shape memory and mechanical property testing.
[0027] As an example, such as Figure 1 As shown, the preparation method of the PEG / PLA high thermal conductivity biodegradable composite film of the present invention includes the following steps: (1) Drying: PLA and PEG were vacuum dried at 60℃ for 8 hours; Al2O3 and BN were vacuum dried at 120℃ for 12 hours; (2) such as Figure 2 As shown, the filler modification was performed as follows: the amount of coupling agent added was 5 wt% of the filler mass, the solvent was anhydrous ethanol / deionized water = 95:5, pH = 5.0, pre-hydrolysis for 30 min, reaction at 60℃ for 4 h, washing with ethanol 3 times, and drying at 80℃ for 12 h. (3) Melt blending: The twin-screw extruder was used to repeat the extrusion process twice at temperature zones of 155℃, 160℃, and 165℃. (4) Hot pressing: 170℃, 10MPa, preheat for 10min, hot press for 10min; prepare 0.55mm film for thermal conductivity test, 0.15mm film for shape memory and mechanical test.
[0028] The following specific examples and comparative examples further explain and illustrate the PEG / PLA high thermal conductivity biodegradable composite film of the present invention, its preparation method, and its application.
[0029] Example 1: The preparation method of the PEG / PLA high thermal conductivity biodegradable composite film in this embodiment includes the following steps: PLA and PEG were placed in a vacuum oven and dried at 60°C for 8 hours; Al2O3 and BN were placed in a vacuum oven and dried at 120°C for 12 hours. KH560 modified Al2O3: Take 20g of Al2O3, add anhydrous ethanol / deionized water (95:5) mixture, add 1g H560 (5wt% of filler mass), adjust pH to 5.0 with glacial acetic acid, stir at room temperature for 30min; after ultrasonic dispersion, stir and react at 60℃ for 3h, filter, wash 3 times with ethanol, and vacuum dry at 80℃ for 12h to obtain K-Al2O3; KH550 modified BN: Take 40g of BN, add anhydrous ethanol / deionized water (95:5) mixture, add 2g of H550 (5wt% of filler mass), adjust pH to 5.0 with glacial acetic acid, stir at room temperature for 30min; after ultrasonic dispersion, stir and react at 60℃ for 3h, filter, wash 3 times with ethanol, and vacuum dry at 80℃ for 12h to obtain K-BN; Weigh 10g of K-Al2O3 and 10g of K-BN, add anhydrous ethanol, disperse by ultrasonication and stirring, and then dry to obtain the composite filler; Weigh 68g of PLA and 12g of PEG (mass ratio 85:15), mix them evenly with the above compound filler; extrude and granulate in the temperature zones of a twin-screw extruder: 155℃, 160℃, 165℃, repeat the extrusion twice to further improve the uniformity of the components and obtain composite granules. Take 2g of composite granules, preheat at 170℃ and 10MPa for 10min, hot press for 10min, cool and demold to obtain 0.55mm thermal conductivity test film and 0.15mm shape memory test film respectively.
[0030] Example 2: The difference between the preparation method of the PEG / PLA high thermal conductivity biodegradable composite film in this embodiment and that in Example 1 is: Raw material ratio: PLA 59.5g, PEG 10.5g, K-Al2O3 10g, K-BN 20g; The remaining preparation steps and process parameters are the same as in Example 1.
[0031] Comparative Example 1: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Only 85g of PLA and 15g of PEG are taken, dried, melt-blended, and hot-pressed, without any thermally conductive fillers added; The remaining preparation steps and process parameters are the same as in Example 1.
[0032] Comparative Example 2: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, unmodified Al2O3 20g, no BN; The remaining preparation steps and process parameters are the same as in Example 1.
[0033] Comparative Example 3: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, unmodified BN 20g, no Al2O3; The remaining preparation steps and process parameters are the same as in Example 1.
[0034] Comparative Example 4: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, unmodified Al2O3 10g, unmodified BN 10g; The remaining preparation steps and process parameters are the same as in Example 1.
[0035] Comparative Example 5: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, K-Al2O3 20g, BN-free; The remaining preparation steps and process parameters are the same as in Example 1.
[0036] Comparative Example 6: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, K-Al2O3 10g, unmodified BN 10g; The remaining preparation steps and process parameters are the same as in Example 1.
[0037] Comparative Example 7: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, K-BN 20g, Al2O3-free; The remaining preparation steps and process parameters are the same as in Example 1.
[0038] Comparative Example 8: The preparation method of the PEG / PLA composite film in this comparative example differs from that in Example 1 in that: Raw material ratio: PLA 68g, PEG 12g, K-BN 10g, unmodified Al2O3 10g; The remaining preparation steps and process parameters are the same as in Example 1.
[0039] The performance of the composite films of the above embodiments and comparative examples is compared below. The thermal conductivity index of the composite films of each embodiment and comparative example is shown in Table 1, and the shape memory performance index is shown in Table 2. Table 1 Thermal conductivity data ; Table 2. Shape Memory Performance Data ; Based on the thermal conductivity test data of each group of samples in Table 1, analyze the variation law and underlying mechanism of thermal conductivity performance: The pure matrix comparative example 1 is composed only of PLA and PEG blend. The polymer matrix is mainly phonon thermally conductive with strong phonon scattering. The room temperature thermal conductivity is only 0.232 W / (m·K), which is the lowest thermal conductivity among all samples. This is used as the comparison benchmark for all samples. The addition of unmodified inorganic fillers improved the thermal conductivity of all materials. However, the thermal conductivity of unmodified alumina in Comparative Example 2 was only 0.300 W / (m·K), showing a limited improvement. The thermal conductivity of unmodified boron nitride in Comparative Example 3 reached 0.523 W / (m·K). This is because the intrinsic thermal conductivity of hexagonal boron nitride is much higher than that of alumina, and its two-dimensional layered structure makes it easier to form basic thermal conduction pathways. However, both types of unfilled materials exhibited agglomeration problems, poor compatibility between the filler and the matrix interface, high interfacial thermal resistance, and a large amount of phonon scattering at the interface, thus significantly limiting the improvement in thermal conductivity. Comparative Example 4, which uses two types of fillers in combination with unmodified Al2O3 / BN, relies on the simple physical superposition of particles and sheets to construct a heat conduction path. The thermal conductivity is 0.458 W / (m·K), which is between the two single unmodified fillers. This indicates that the simple physical combination cannot overcome the limitation of interfacial thermal resistance. The two fillers cannot form an effective overlap, the synergistic effect is weak, and the thermal conductivity has not achieved a leapfrog improvement. Comparative Example 5, with only modified alumina as the single filler, and Comparative Example 6, with only modified alumina as the composite filler, only underwent surface modification of alumina, without treating boron nitride. The filler system still exhibited numerous interfacial defects, and its thermal conductivity was essentially the same as the corresponding unmodified sample, indicating an insignificant modification effect. Comparative Example 5, with only modified boron nitride as the single filler, achieved a thermal conductivity of 0.563 W / (m·K), a slight improvement compared to the unmodified boron nitride comparative example. This is because boron nitride, as the dominant thermally conductive phase, showed improved dispersion and interfacial bonding through surface modification, resulting in a slight reduction in interfacial thermal resistance. Comparative Example 6, with only modified boron nitride as the composite filler, still suffered from interfacial defects due to the lack of alumina modification, resulting in a minimal increase in thermal conductivity. These results demonstrate that modifying only a single filler cannot completely solve the interfacial thermal resistance problem of the system and is insufficient to significantly improve thermal conductivity.
[0040] In Examples 1 and 2, KH560 and KH550 were used to modify alumina and boron nitride through a dual-interface process. The epoxy groups and amino groups on the filler surface reacted to form an interfacial bridging structure, which fundamentally inhibited filler agglomeration and reduced the interfacial thermal resistance between fillers and between fillers and the matrix. At the same time, spherical alumina filled the gaps between boron nitride layers, and the two formed a continuous and complete three-dimensional thermally conductive network. The thermal conductivity of Example 1 was 0.563 W / (m·K), which was comparable to the comparative example with fully modified boron nitride filler when only half the amount of boron nitride was used. Example 2 increased the amount of boron nitride added, further increasing the density of thermal conductivity pathways, and the room temperature thermal conductivity reached 0.815 W / (m·K), which was 243.9% higher than the pure matrix comparative example and 52.9% higher than the optimal unmodified system, showing a very significant improvement.
[0041] In addition, temperature variation tests were conducted on the embodiments. The decreasing trend of thermal conductivity at 25℃, 40℃, and 60℃ indicates that the thermal conductivity of this sample is mainly conducted by the filler network. The increase in temperature will intensify the phonon scattering at the interface, resulting in a slight decrease in thermal conductivity, which is consistent with the thermal conductivity variation law of filled polymer composite materials.
[0042] Based on the shape memory test data of each group in Table 2, the shape memory performance of the composite film was analyzed: Comparative Example 1, which contains no inorganic filler, achieves a shape recovery rate (Rr) of 100.00% and a shape fixation rate (R...). f The recovery rate was 97.78%, making it the best among all samples and serving as the reference standard for this experiment.
[0043] Comparative Examples 2 and 3 were filled with unmodified alumina and unmodified boron nitride, respectively. The two types of fillers showed poor interfacial compatibility, easily agglomerating to form a rigid barrier network, significantly hindering the rebound of molecular chains upon heating. Their maximum recovery rates were only 78.29% and 70.62%, respectively, indicating a significant deterioration in shape memory performance. Comparative Example 4 used a combination of unmodified alumina and boron nitride. The interpenetration of spherical particles and lamellar morphology disrupted the continuous stacking structure of the single filler, increasing the channels for molecular chain movement and raising the recovery rate to 91.38%, thus mitigating some performance degradation. However, physical interpenetration alone could not eliminate interfacial defects between the filler and the matrix, and the performance was still inferior to Comparative Example 1. Comparative Example 5 was a single KH560 modified alumina sample. Its maximum recovery rate recovered to 100.00%, on par with the blank sample, demonstrating that silane-modified alumina significantly promoted the shape memory performance of the thin film. KH560 grafts flexible organic chains onto the alumina surface, improving the interfacial compatibility between the filler and the PEG / PLA matrix, inhibiting particle agglomeration, and the flexible silane layer does not form a rigid barrier, thus not hindering the reversible stretching and relaxation of the polymer chains, and therefore fully preserving the material's deformation recovery capability. In contrast, Comparative Example 7, which only modifies boron nitride, is limited by the easy stacking characteristics of BN sheets, still resulting in a large area of bound molecular chains, with a maximum recovery rate of only 66.29%, the lowest among all samples.
[0044] Comparative Examples 6 and 8 are composite systems of a single modified filler combined with another type of unmodified filler. The unmodified filler is prone to agglomeration, forming rigid barriers that negate the interface optimization effect brought by the modified alumina, resulting in poor recovery performance. Examples 1 and 2 are the dual-modified composite systems of this invention. In Example 2, the total amount of filler added is higher than in all comparative examples. The modified alumina can optimize the interface and alleviate chain segment binding, but some modified boron nitride sheets in the system still have a stacking barrier effect. Therefore, the maximum recovery rate of Example 2 is slightly lower than that of Comparative Example 4. However, thanks to the interface promoting effect of the modified alumina, and the formation of a flexible organic bridging layer during the melt processing of the two types of modified fillers, the performance degradation caused by high filling is minimized. While achieving thermal conductivity far higher than all control groups, the maximum recovery rate of the film is around 90%, and the shape fixation rate is stably maintained at over 98%, retaining the thermally induced shape memory effect with practical value. This solves the contradiction of insufficient thermal conductivity with low filling and significant reduction in deformation capacity with high filling in traditional filler systems.
[0045] The mechanism of this invention is analyzed as follows: (1) Mechanism of filler surface modification: After hydrolysis, KH560 generates silanol, which condenses with hydroxyl groups on the Al2O3 surface to form Si-O-Al covalent bonds, introducing epoxy groups to the filler surface; after hydrolysis, KH550 combines with active sites at the edges and defects of the BN surface to form a Si-OB structure, introducing amino groups to the filler surface. FT-IR and XPS test results confirmed that the coupling agent was successfully grafted onto the filler surface without damaging the filler bulk structure. TGA test further verified that the modified filler has good thermal stability and can meet the processing requirements of this invention; (2) Interface bridging and heat conduction network mechanism: such as Figure 3 As shown, during melt blending and hot pressing, the epoxy groups on the surface of K-Al2O3 and the amino groups on the surface of K-BN undergo a ring-opening reaction to form a K-Al2O3-coupling agent-K-BN interfacial bridging structure. This structure improves the interfacial compatibility between the inorganic filler and the PEG / PLA matrix, inhibits filler agglomeration, and reduces internal pores and defects in the matrix. On the other hand, it reduces the interfacial thermal resistance between fillers and between fillers and the matrix, reducing phonon scattering. At the same time, the two-dimensional lamellar BN forms the main thermal conduction pathway, while the spherical Al2O3 fills the gaps between the lamellars and acts as a bridge. Together, they construct a continuous and dense three-dimensional thermal conduction network, significantly improving heat transfer efficiency. (3) The mechanism of shape memory degradation caused by inorganic fillers and the improvement mechanism of the present invention: Unmodified Al2O3 and BN are high-rigidity inorganic fillers. After direct blending, a large number of particles / sheets are interspersed between polymer chains, forming physical binding sites. During the low-temperature shaping and stretching stage, the molecular chains are blocked by the rigid fillers and cannot fully store the deformation, resulting in a decrease in shape fixation rate. During the temperature recovery stage, the fillers increase the chain segment relaxation resistance, and the deformation cannot fully rebound, resulting in a significant decrease in shape recovery rate. After the fillers agglomerate, the binding effect is superimposed, and the degree of shape memory degradation is aggravated. The flexible silane bridging layer constructed in this invention can buffer the blocking effect of the rigid fillers. The fillers are uniformly and monodisperse without large-scale agglomeration, leaving sufficient space for the reversible movement of PLA and PEG molecular chains. Even with high filler content, the film can still complete the complete deformation storage and temperature recovery, solving the core contradiction between thermal conductivity and shape memory. (4) Crystallization enhancement mechanism: Unmodified fillers can only slightly improve the crystallization ability of PLA, and are prone to spatial constraints due to agglomeration, which restricts crystal growth; the modified filler of this invention is uniformly dispersed and can serve as a large number of heterogeneous nucleation sites, inducing PLA molecular chains to arrange in an orderly manner, thereby improving crystallinity and crystal perfection. DSC test confirmed that the modified filler can change PLA from "cold crystallization by heating" to "direct crystallization by cooling", and the thermal stability of the material is significantly improved; This invention focuses on optimizing the thermal conductivity of composite films, while also addressing the industry pain point of inorganic fillers damaging shape memory properties. Through a dual-filler compounding and dual-silane coupling agent interface synergistic modification scheme, the thermally induced shape memory capability of the film is stably maintained while significantly improving thermal conductivity. The process is simple, the raw materials are readily available, and it can be applied to various thermally conductive deformation-related scenarios.
[0046] Given that there are numerous embodiments of the present invention, the raw materials and amounts involved can be selected within a limited range according to actual needs, and the experimental data of each embodiment are extensive and numerous, it is not suitable to list and describe them one by one here. However, the content to be verified and the final conclusions obtained in each embodiment are similar.
[0047] The above description is merely a detailed explanation of preferred embodiments and principles of the present invention, and is intended to benefit those in the art. For those skilled in the art, there may be changes in the specific implementation based on the ideas provided by this invention, and these changes should also be considered within the scope of protection of this invention.
Claims
1. A PEG / PLA high thermal conductivity biodegradable composite film, characterized in that, It includes an organic matrix phase and modified inorganic non-metallic thermally conductive fillers distributed in the organic matrix phase; The organic matrix phase is a blend of polylactic acid (PLA) and polyethylene glycol (PEG). The modified inorganic non-metallic thermally conductive filler is a composite filler consisting of γ-glycidoxypropyltrimethoxysilane-modified alumina K-Al2O3 and γ-aminopropyltriethoxysilane-modified hexagonal boron nitride K-BN.
2. The PEG / PLA high thermal conductivity biodegradable composite film according to claim 1, characterized in that, Based on a total mass of 100 parts, the mass ratio of each component is as follows: PLA 59.5-68 parts, PEG 10.5-12 parts, K-Al2O3 5-10 parts, and K-BN 10-20 parts.
3. The method for preparing the PEG / PLA high thermal conductivity biodegradable composite film as described in claim 2, characterized in that, Includes the following steps: (1) K-Al2O3 and K-BN were prepared by surface grafting modification of Al2O3 and BN respectively using γ-glycidoxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane. (2) K-Al2O3 and K-BN were added to anhydrous ethanol, stirred and ultrasonically dispersed, and then dried to remove the solvent to obtain modified inorganic non-metallic thermally conductive filler. (3) The dried PLA and PEG are mixed evenly with the modified inorganic non-metallic thermally conductive filler, and then melt-blended, extruded and pelletized to obtain composite granules; (4) The composite granules are hot-pressed to obtain a PEG / PLA high thermal conductivity biodegradable composite film.
4. The preparation method according to claim 3, characterized in that, In step (1), the surface grafting modification process includes: The silane coupling agent γ-glycidoxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane was added to a mixture of anhydrous ethanol and water, and the pH was adjusted to 4.5-5.5 with glacial acetic acid. The mixture was pre-hydrolyzed at room temperature for 10-30 min. The corresponding filler, alumina Al2O3 or hexagonal boron nitride BN, was added, and the mixture was stirred at 60-80℃ for 2-4 h. After filtration, the mixture was washed with anhydrous ethanol and dried under vacuum to obtain K-Al2O3 or K-BN.
5. The preparation method according to claim 4, characterized in that, The amount of the silane coupling agent added is 3 to 5 wt% of the filler mass.
6. The preparation method according to claim 4, characterized in that, The volume ratio of anhydrous ethanol to water in the mixture is (90-95):(5-10) per 100 parts by volume.
7. The preparation method according to claim 4, characterized in that, The particle size of Al2O3 is 5-10 μm, and the particle size of BN is 25 μm.
8. The preparation method according to claim 3, characterized in that, The step (3) is carried out in a twin-screw extruder, and the temperatures of the three heating zones are set to 155℃, 160℃ and 165℃ respectively.
9. The preparation method according to claim 3, characterized in that, In step (4), the hot pressing temperature is 160-180℃, the pressure is 5-10MPa, the preheating time is 5-10min, and the hot pressing time is 5-10min.
10. The application of the PEG / PLA high thermal conductivity biodegradable composite film as described in claim 1 or 2, or the PEG / PLA high thermal conductivity biodegradable composite film prepared by the preparation method as described in any one of claims 3-9, characterized in that, Used in flexible electronics, wearable devices, electronic packaging, thermal management materials, and biodegradable shape memory smart packaging materials.